Additive manufacturing technology and material selection for direct manufacture of products based on computer aided design geometric feature analysis. (1st January 2012) - Smith, Paul C.; Lupeanu, Mihaela-Elena; Rennie, Allan E.W.
This paper presents research into the development of an algorithm developed in a Visual Basic programming environment that aids in the selection of materials processed using additive manufacturing (AM) technologies. AM technologies such as selective laser sintering (SLS) and fused deposition modelling (FDM) have limitations on the materials available to them and each system has factors that limit the geometric freedom of the components that they can produce. Thus, materials capable of being processed on these types of technology can be selected through a method of traversing the geometric features of a computer aided design (CAD) model and performing an analysis of each individual feature's attributes. The algorithm developed for this research uses data based on minimum feature size and a model bounding box as criteria in the selection of suitable materials. Through integration with an existing commercially available CAD software package, a component can be automatically analysed for its geometric feature properties and attributes, returning suitable AM systems and material information for selection by the operator. A number of case studies are presented that highlight the successful operation of the AM technology and material selection tool that has been developed.